Cardiovascular Safety and Benefits of Testosterone Implant Therapy in Postmenopausal Women: Where Are We? - Guilherme Renke; Francisco Tostes (MDPI AG, 2023)
We discuss the CV safety and efficacy data for subcutaneous testosterone therapy (STT) in postmenopausal women. We also highlight new directions and applications of correct dosages performed in a specialized center. To recommend STT, we propose innovative criteria (IDEALSTT) according to total testosterone (T) level, carotid artery intima-media thickness, and calculated SCORE for a 10-year risk of fatal cardiovascular disease (CVD). Despite all the controversies, hormone replacement therapy (HRT) with T has gained prominence in treating pre and postmenopausal women in the last decades. HRT with silastic and bioabsorbable testosterone hormone implants has gained prominence recently due to its practicality and effectiveness in treating menopausal symptoms and hypoactive sexual desire disorder. A recent publication on the complications of STT, looking at a large cohort of patients over seven years, demonstrated its long-term safety. However, the cardiovascular (CV) risk and safety of STT in women are still controversial.